The impact of selected financial indicators related to the structure of funding sources on corporate liquidity in energy sector in the Czech republic and Slovak republic - Šeligová, Markéta (Univerzita Pardubice, 2018)
The aim of this paper is to determine the impact of selected financial indicators related to the structure of funding sources on liquidity of companies in energy sector in the Czech Republic and Slovak Republic. With the purpose to fulfill the aim, we examine existence and character of relationship between selected financial factors (debt equity ratio, return on equity, share of fixed assets to total assets, share of earnings before interest and taxes to total assets, equity ratio) and liquidity of the companies in energy sector in the Czech Republic and Slovak Republic. The existence of relationship between financial factors and liquidity of companies is tested by correlation analysis and generalized method of moments called GMM method. We found that corporate liquidity was positively influenced by the equity ratio and return on equity in energy sector in the Czech Republic. We found that corporate liquidity was positively influenced by the equity ratio and share of earnings before interest and taxes to total assets in energy sector in the Slovak Republic. On the other hand, we found that corporate liquidity was negatively influenced by the share of earnings before interest and taxes to total assets, share of fixed assets to total assets in the Czech Republic. We found that corporate liquidity was negatively influenced by the share of fixed assets to total assets in energy sector in the Slovak Republic.
Keywords: correlation; debt equity ratio; fixed assets; generalized method of moments; leverage ratio; liquidity; return on equity; G32; G34; G39